PERTUMBUHAN VEGETATIF-GENERATIF KELAPA SAWIT: STUDI KASUS PERBEDAAN JENIS TANAH DI KALIMANTAN BARAT - Nurcahyono Nurcahyono; Julsento HP; Herlina Mega Puspitasari; Wandha Atmaka Aji (AGRICA, 2026)
Oil palm (Elaeis guineensis Jacq.) is a strategic commodity in Indonesia whose productivity is strongly influenced by environmental conditions, particularly soil type, which serves as the primary growing medium. This study aims to analyse the effect of various soil types on the vegetative and generative growth of oil palm in West Kalimantan. The study was conducted using a Completely Randomised Design (CRD) with four soil types moderate acid sulfate soil, deep acid sulfate soil, low soil, and mineral soil each replicated 5 times. Observed parameters included plant height, stem diameter, frond width, and number of flowers and fruits, which were then analysed using ANOVA and DMRT at a 95% confidence level. The results showed that soil type significantly affected plant height, with deep acid sulfate soil producing the highest average (4.1 m). In contrast, stem diameter, frond width, and the number of flowers and fruits did not differ significantly between soil types. This finding confirms that the characteristics of deep acid sulfate soil are more supportive of vegetative growth. Still, generative growth is more influenced by agronomic factors such as fertilization and water availability. In this regard, this research provides a scientific basis for applying the soil-adaptive cultivation concept to increase the productivity and sustainability of oil palm plantations across various soil conditions in Indonesia.